Productos y servicios financieros a gran escala para la microempresa: hacia un modelo viable (2004)
This work proposes a model by means of which the commercial banks can sell products and financial services on great scale to the microenterprise. The exposition of this model is the result of the revision of some part of literature available in relation to the subject and of a personal contribution. The model leaves from the base that it is the great commercial banking the one called to sell products and financial services on great scale to the microenterprise, implementing the microenterprise banking and penetrating this segment of market or, as it is said in international marketing slang, doing downscaling. A set of critical variables is identified and it is considered how they must be defined to considerably increase the probability that the product and financial services commercialization on great scale to the microenterprise is viable and sustainable in the time. Finally, the results corresponding to the Study of Opportunity for the project "Products and financial services on great scale for the Colombian microenterprise", are analyzed based on the proposed model and following the methodology for the study of projects of the United Nations Industrial Development Organization (UNIDO).